Critical Analysis of Attainment of Arabic Language Learning Outcomes in Competency-based Curriculum at Elementary Islamic Schools - Nurwinanda, Nurwinanda; Khalik, Muh. (Research Horizon, 2023)
This research aims to assess students’ proficiency in the 2004 competency-based curriculum for learning Arabic. Employing a qualitative descriptive approach, the study thoroughly delves into the subject matter, providing a comprehensive and detailed analysis. The data analysis methodology raises concerns about the quality of teaching aids employed in Grade V of Madrasah Ibtidaiyah (MI) for Arabic language instruction. The findings of this study reveal that the case falls short of meeting the criteria for all four 2004 Competency-Based Curiculum (CBC) competencies. The academic competence lacks clarity as the instructional approach primarily focuses on mastering hiwar, qira’ah, and insya’ muwajjah (dialogue, reading, and directed writing); occupational competence does not establish a tangible connection with real-world application for students; cultural competence does not incorporate materials that promote appreciation for student diversity; and temporal competence fails to establish relevant material connections. The absence of these competencies in the curriculum renders the four language skills inconsequential to students’ proficiency in studying Arabic in Grade V of MI under the 2004 PBC. Consequently, further studies are imperative to ensure the effective implementation of CBC across all educational levels, including Madrasah Ibtidaiyah, Madrasah Tsanawiyah, and Madrasah Aliyah.